PENYEDIAAN BROODSTOCK IKAN LELE DUMBO (Clarias gariepinus) MENGGUNAKAN TEKNOLOGI LASERPUNKTUR SEBAGAI UPAYA PENYEDIAAN BENIH SKALA MASSAL - Pungky Slamet Wisnu Kusuma (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2008)
The aim of this research was to increase growth rapid, maturity, and shorthening catfish reproduction cycle in order to produce catfish’s broodstock continously, specially in Boyolali regency. Research was carried out at Janti, Klaten from July to November 2007. The research was an experimental research which tested two groups. One group is control group that used catfish without any treantment, and the other is a group of catfish which is treated by laser. Parameters used in this research are the growth of catfish, Gonad Maturity Index, Gonad Maturity Level, time of maturity and reproduction cycle. Data was analyzed by descriptive analysis and t test. The results show that soft laser shooting on the governoer vessel of catfish would give influence in catfish’s growth, Gonad Maturity Index, Gonad Maturity Level, time of maturity and reproduction cycle. The use of laser shooting not depend on season.